Importance of anaerobic ammonium oxidation as a nitrogen removal pathway in freshwater marsh sediments - Shen, L.‐D.; Liu, X.; Wu, H.‐S. (Journal of applied microbiology, 2018)
Aims To explore the role of anaerobic ammonium oxidation (anammox) in nitrogen removal in freshwater marshes. Methods and Results The 16S rRNA gene sequences of Candidatus Kuenenia and Candidatus Brocadia were simultaneously detected in the sediment of freshwater marshes of Green Bay Wetland that is located in Eastern China by using Illumina‐based sequencing of the total bacterial 16S rRNA genes, and Candidatus Brocadia comprised more than 80% of the total anammox‐related sequences. The abundance of anammox bacteria was determined by quantitative PCR on their hydrazine synthase (hzs) genes, which ranged from 3·13 × 104 to 1·58 × 105 copies per g sediment with little temporal variation. The potential anammox rates measured by 15N‐stable isotope pairing technique were 0·78–5·37 nmol N g−1 sediment per h, accounting for 4·3–38·5% of total sediment dinitrogen gas (N2) production. Both the anammox activity and its contribution to N2 production were sensitive to temporal variation and correlated well with the sediment NO3− content. To further examine the nitrogen removal potential via anammox, batch culture was set‐up to enrich anammox bacteria from the marsh sediments. Both the activity and abundance of anammox bacteria increased significantly after 6 months of incubation, varying from 61·6 to 95·8 nmol N g−1 sediment per h and 2·86 × 105 to 6·58 × 105 copies per g sediment respectively. Conclusions Our results revealed the great potential of anammox in nitrogen removal in freshwater marshes. Significance and Impact of the Study This is the first study to show the anammox activity and its temporal variation in freshwater marsh sediments, which improved our understanding of nitrogen removal mechanisms in freshwater marshes.